1991
DOI: 10.1002/cne.903120110
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural changes in the nucleolus of facial motor neurons following axotomy during an early critical period in development

Abstract: In this study, the effects of axotomy on the ultrastructure of the nucleolus and associated organelles were examined in fetal, newborn, and early postnatal facial motoneurons of the hamster. Golden hamsters used for this study were the 14-day fetus, newborn (0 days; less than 6 hr) and 2, 4, 7, and 9 days postnatal ages, with 3 animals per group. For prenatal surgeries, pregnant hamsters were anesthetized and the facial nerves severed in the fetuses via electrocautery through the uterine wall and amniotic memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

1992
1992
2003
2003

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…Peripheral nerve lesions are known to induce several morphological (16), biochemical (20)(21)(22)(23), and physiological (17)(18)(19) changes in a-motoneurons. The alterations in a-motoneuron physiological properties seen after sciatic nerve lesions are known to be reversible upon target reinnervation (33)(34)(35) and have been ascribed primarily to the loss of functional contact with the muscular targets, since they can be reproduced by the intramuscular administration of botulinum toxin (36) and are not prevented by chronic electric stimulation (37).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Peripheral nerve lesions are known to induce several morphological (16), biochemical (20)(21)(22)(23), and physiological (17)(18)(19) changes in a-motoneurons. The alterations in a-motoneuron physiological properties seen after sciatic nerve lesions are known to be reversible upon target reinnervation (33)(34)(35) and have been ascribed primarily to the loss of functional contact with the muscular targets, since they can be reproduced by the intramuscular administration of botulinum toxin (36) and are not prevented by chronic electric stimulation (37).…”
Section: Discussionmentioning
confidence: 99%
“…After peripheral nerve lesions, motoneurons undergo complex morphological (16), physiological (17)(18)(19), and biochemical (20)(21)(22)(23)) changes. We have tested whether the presumptive Renshaw neurons might respond to peripheral nerve injuries by modulating their calbindin-expression as a result of the reduced motoneuronal activity and the consequent reduced need for Ca2+-buffering power.…”
mentioning
confidence: 99%
“…It is most likely that sex differences in nucleolar size are also present in other sexually dimorphic system, but this special feature has not been investigated, so far. During development, changes in nucleolar size have been observed in facial motor neurons (Clark et al, 1991). The nucleolus of these neurons matures progressively from a small, densely compact structure to a large one having a distinctly reticulated organization early in development.…”
Section: Developmental Changes In Nucleoli Are Onlymentioning
confidence: 99%
“…Evidence obtained from numerous systems has demonstrated that the nucleolus, site of polymerase I-directed ribosomal RNA transcription and processing, is one of the earliest cellular organelles to be affected by axon disconnection from the periphery (Watson, 1968;Lieberman, 1971;Jones and LaVelle, 1986). Ultrastructural analysis of axotomized FMN nucleoli in developing and adult hamsters suggests that a key step in the ability of these neurons to survive injury and successfully regenerate occurs at some point in rRNA transcription, processing, or both (Kinderman and LaVelle, 1976;Jones and LaVelle, 1986;Clark et al, 1991). Steroid hormones have also been shown to regulate ribosomal gene expression and nucleolar ultrastructure (Cohen and Pfaff, 1981;Whelly, 1985;Jones et al, 1990).…”
mentioning
confidence: 98%
“…It is unknown, however, which aspects of ribosome biogenesis are altered by axotomy and what effects steroid hormone treatment coincident with injury might have on the nucleolar reaction. The morphologic evidence presented in the hamster FMN system suggests that axotomy induces changes in rRNA transcription, rather than stability (Jones and LaVelle, 1986;Clark et al, 1991). In this study, we used molecular and stereologic approaches to determine the effects of both axotomy and steroid treatment on rRNA transcription and processing in axotomized hamster FMN.…”
mentioning
confidence: 99%